Penegakan Hukum terhadap Ayah yang Lalai Menafkahi Anak Pasca-Perceraian: Analisis Pidana dan KHI - Ana Laela Fatikhatul Choiriyah; Ni Putu Ratnayutika; Inayatul Anisa (SAKINAH: Jurnal Hukum Keluarga Islam, 2025)
Abstract: This study examines the enforcement of law against fathers who neglect child support obligations after divorce within the framework of Islamic family law and criminal law in Indonesia. Although the Marriage Law and the Compilation of Islamic Law stipulate that fathers are responsible for their children’s needs, in practice, enforcement and monitoring mechanisms remain weak. As a result, many mothers bear a double burden while children suffer from neglect. From a criminal law perspective, such negligence may constitute child neglect under the Child Protection Law. This research also compares Malaysia’s system, which is more effective through the establishment of special institutions such as the Family Support Division (BSK). The analysis employs Feminist Legal Theory and the Theory of Children’s Rights, emphasizing the need for substantive justice for women and the protection of children’s rights to care, education, and welfare. The findings highlight the urgency of legal reform in Indonesia so that child support rulings are not merely declaratory but truly ensure comprehensive protection for women and children. Keywords: Child Support, Divorce, Religious Court   Abstrak: Penelitian ini membahas penegakan hukum terhadap ayah yang lalai menafkahi anak pasca perceraian dalam perspektif hukum keluarga Islam dan hukum pidana di Indonesia. Meskipun Undang-Undang Perkawinan dan Kompilasi Hukum Islam telah menetapkan kewajiban ayah untuk membiayai kebutuhan anak, praktik di lapangan menunjukkan lemahnya mekanisme pengawasan dan eksekusi putusan nafkah. Akibatnya, banyak ibu menanggung beban ganda, sementara anak menjadi korban penelantaran. Dari perspektif hukum pidana, kelalaian ini dapat dikategorikan sebagai penelantaran anak berdasarkan Undang-Undang Perlindungan Anak. Penelitian ini juga membandingkan sistem di Malaysia yang lebih efektif melalui pembentukan lembaga khusus seperti Bahagian Sokongan Keluarga (BSK). Analisis menggunakan pendekatan Feminist Legal Theory dan Teori Hak Asasi Anak, yang menegaskan pentingnya keadilan substantif bagi perempuan dan pemenuhan hak anak atas pengasuhan, pendidikan, dan kesejahteraan. Hasil kajian menunjukkan urgensi reformasi hukum di Indonesia agar putusan nafkah anak tidak hanya bersifat deklaratif, melainkan benar-benar menjamin perlindungan perempuan dan anak secara komprehensif. Kata Kunci: Nafkah Anak, Perceraian, Pengadilan Agama